Isolation and screening of pectinase producing bacteria from rotten fruits - Abdul Wahid, Amirah Adibah (2015)
Production of enzymes from bacteria for example pectinase has high demand from industry especially for cost-effective production process in food industry. Besides, redundancy of agricultural wastes is also a concern that need to be handled. Waste materials from agricultural activities might be one of the resources that we can take as in order to be used in the production of the enzymes such as pectinase. Hence, in this study, pectinolytic bacteria were isolated from four rotten local fruits which were watermelon, lime, banana and mango in yeast extract pectin (YEP) agar medium. The best pectinase producing bacteria isolated among the four was identified as Bacilus sp. and labeled as Bacillus sp. WM 3. The bacteria was then studied for its pectinase activity and specific pectinase activity. The maximum enzyme activity of the crude enzyme extract was 4.383 U/ml at 30°C with agitation and incubated for 5 days. From this study, we have discovered the potential bacterial species that can produce significant pectinase amount.